2012
DOI: 10.1007/978-3-642-34898-3_8
|View full text |Cite
|
Sign up to set email alerts
|

Combining Implicit and Explicit Methods for the Evaluation of an Ambient Persuasive Factory Display

Abstract: Abstract. Research in ambient intelligent systems faces a challenging endeavor, namely the evaluation of user experience of ambient displays. Due to the fact that ambient displays should be unobtrusive, it is hard for users to appraise them on a reflective level (i.e. interviews and questionnaires). In this paper we present a methodological approach that combines an implicit (the Affect Misattribution Procedure (AMP)) and an explicit measurement technique (questionnaire for the persuasive effect (PeQ)) to tack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Furthermore, the studies were the basis for designs and UX prototypes. In these designs, we focused on wearable devices [26], [28], or ambient, persuasive displays in the factory [7], [22], [23], [36].…”
Section: Overview On Materials Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the studies were the basis for designs and UX prototypes. In these designs, we focused on wearable devices [26], [28], or ambient, persuasive displays in the factory [7], [22], [23], [36].…”
Section: Overview On Materials Usedmentioning
confidence: 99%
“…How easy the interface is to handle in the interaction [7], [17], [18], [23] Performance Expectancy Degree to which a worker believes that using the system will support his/her performance [31], [34], [35], [36] Satisfaction Workers' contentment with the interaction [17], [18], [33], [35], [44]…”
Section: Perceived Ease Of Usementioning
confidence: 99%
“…We aim to evaluate all our novel contextual interfaces at some point by the means of observational studies in the factory (taking into account the lessons learned, such as the need for expert discussions before the observation and the company of a technician to discuss behavior observations in parallel). A first "in-the-wild" study was already conducted to explore the actual usage of the Operator Guide and showed us unexpected usages and interpretations of the display (see Strasser et al 2012).…”
Section: Evaluation Of Cleanroom Redesigns: Field Vs Lab Trialsmentioning
confidence: 99%
“…Thereby, we built our own "HCI-semiconductor experience laboratory," which allows us to study redesigns before going back into the factory. By means of this system, we already successfully evaluated the Operator Guide in a laboratory setting (Strasser et al 2012). However, another challenge that needed to be solved was the recruitment of representative study participants.…”
Section: Evaluation Of Cleanroom Redesigns: Field Vs Lab Trialsmentioning
confidence: 99%
“…We believe that in a context where it is required to apply carefully adjusted measures in order to avoid affecting user experience evaluation [11], experience prototypes can be a valuable mean to communicate design ideas to industrial stakeholders and to transport the wearable interaction paradigm into the context of a semiconductor factory. To transport such an interaction paradigm in this context is challenging due to a variety of factors that need to be considered.…”
Section: Introductionmentioning
confidence: 99%